The Australian Work Exposures Study: Prevalence of Occupational Exposure to Respirable Crystalline Silica - Si, Si; Carey, R.; Reid, A.; Driscoll, T.; Glass, D.; Peters, S.; Benke, G.; Darcey, E.; Fritschi, L. (Oxford University Press, 2016)
Background: Respirable crystalline silica (RCS) is a biologically active dust that can accumulate in the lung and induce silicosis and lung cancer. Despite occupational exposure being the predominant source, no study has described current occupational RCS exposure on a national scale in Australia. The aim of this study is to estimate the characteristics of those exposed and the circumstances of RCS exposure in Australian workplaces. Methods: A cross-sectional survey of the Australian working population (18–65 years old) was conducted. Information about the respondents’ current job and their demographic characteristics was collected in a telephone interview. Occupational exposure to RCS was determined based on preprogrammed decision rules regarding potential levels of exposure associated with self-reported tasks. Results: Overall, 6.4% of respondents were deemed exposed to RCS at work in 2012 (3.3% were exposed at a high level). The exposure varied with sex, state of residence, and socioeconomic status. Miners and construction workers were most likely to be highly exposed to RCS when performing tasks with concrete or cement or working near crushers that create RCS-containing dusts. When extrapolated to the entire Australian working population, 6.6% of Australian workers were exposed to RCS and 3.7% were highly exposed when carrying out tasks at work. Conclusion: This is the first study investigating occupational RCS exposure in an entire national working population. The information about occupational tasks that lead to high level RCS exposure provided by this study will inform the direction of occupational interventions and policies.